A Survey of Five Plant Viruses in Weeds and Tobacco in Poland - Grażyna Korbecka-Glinka (Agronomy, 2021)
Weeds may contribute to the spread of plant virus epidemics by acting as reservoirs of viruses or/and their vectors. The aim of this research was to study the prevalence of five viral pathogens in weeds in the fields of solanaceous crops in six provinces in Poland differing with soil and climate conditions. Most of the sampled sites were associated with tobacco production. The total number of 157 samples of tobacco and 600 samples of weeds were subjected to DAS-ELISA detection of tomato spotted wilt orthotospovirus (TSWV), cucumber mosaic virus (CMV), potato virus Y (PVY), tobacco mosaic virus (TMV) and tobacco ringspot virus (TRSV). Twenty nine percent of samples of weeds were infected with at least one virus. TSWV and TMV were the most frequently detected in 17.5% and 14.7% of samples, respectively. In most provinces where infected tobacco was found, the same virus was also detected in weeds. Results of this survey are discussed in the context of the current status of virus epidemics in tobacco fields in Poland.